Telehealth for Adolescent Mental Health: A Narrative Review of effectiveness, acceptability, and ethical–legal considerations - Munjiza Jovanovic, Ana; Pejovic-Milovancevic, Milica; Mitkovic-Voncina, Marija; Pesic, Danilo (Medical Research, 2026)
Adolescents experience a high burden of mental health problems but face substantial barriers to care. Telehealth—encompassing synchronous teletherapy, telephone contacts, and digital mental health interventions (apps, internet CBT)—has expanded rapidly, especially since the COVID-19 pandemic. The primary purpose of this narrative review was to synthesize current evidence on the effectiveness, acceptability/engagement, clinical safety, and ethical-legal aspects of telehealth interventions in adolescent mental health, with attention to regional regulatory gaps. The reviewed data suggests that telehealth modalities (video, telephone, and digital interventions) can deliver clinically meaningful improvements for common adolescent conditions (depression, anxiety) and, in many settings, achieve outcomes comparable to those of treatment-as-usual. Acceptability among adolescents is generally high but variable and depends on privacy, platform usability, and perceived therapeutic relationship. Remote care raises distinct safety challenges (managing suicidality and crisis response), and the ethical-legal landscape remains underdeveloped in many regions: data protection, consent/assent rules for minors, professional licensure across jurisdictions, and reimbursement policies are recurrent concerns. The supplied reports emphasize important local/regional gaps—limited regulation, infrastructure barriers, and the need for formal protocols and clinician training. In conclusion, telehealth is a viable modality for adolescent mental health care when implemented with clear clinical protocols, robust data‑security safeguards, and attention to consent and crisis pathways. Policy action is required to standardize legal and ethical frameworks, ensure equitable access, and integrate telehealth within routine adolescent mental health services. Keywords: telehealth, adolescents, mental health